HOMEWORK AND THE WELL-BEING OF ELEMENTARY SCHOOL CHILDREN: A CONCEPTUAL CRITIQUE OF CONVENTIONAL LEARNING PRACTICES - Moh Nadhif; Imam Alfafan; Ahmad Naweed Rahimi khamosh (STAI Ma'had Aly Al-Hikam Malang, 2026)
This study critically examines the practice of homework (PR) in elementary schools from the perspective of child well-being. Although homework has long been regarded as a pedagogical instrument to reinforce learning outcomes, discipline, and academic achievement, recent debates highlight its potential psychological and relational consequences for young learners. Using a qualitative approach with a library research design, this study synthesizes relevant scholarly literature on homework practices, student motivation, parental involvement, and holistic child development in basic education. Data were collected from academic journal articles, dissertations, and related scholarly sources, and analyzed through thematic content analysis to identify recurring patterns and conceptual tensions. The findings reveal four major insights. First, homework demonstrates academic ambivalence: while it may support cognitive reinforcement, excessive and repetitive assignments can reduce intrinsic motivation. Second, homework creates structural dependence on parental assistance, which may intensify inequality among students from diverse family backgrounds. Third, the dominance of academic logic in homework practices often constrains children’s rights to play, rest, and build meaningful family interactions. Fourth, emerging discussions on homework-free policies suggest the need for reconstructing conventional learning paradigms in elementary education. Based on these findings, this study proposes a conceptual model of homework reorientation centered on three pillars: classroom learning optimization, balanced child development time, and proportional school–parent educational partnership. The model emphasizes that effective education in elementary schools should not rely primarily on increasing academic workload outside school hours, but on enhancing meaningful learning experiences and safeguarding children’s psychological and social well-being. This research contributes theoretically to critical discourse in basic education by positioning child welfare as a central criterion in evaluating homework policies and conventional instructional practices.